Radiographic lung volumes predict progression to COPD in smokers with preserved spirometry in SPIROMICS. Issue 4 (31st October 2019) - Arjomandi, Mehrdad; Zeng, Siyang; Barjaktarevic, Igor; Barr, R. Graham; Bleecker, Eugene R.; Bowler, Russell P.; Buhr, Russell G.; Criner, Gerard J.; Comellas, Alejandro P.; Cooper, Christopher B.; Couper, David J.; Curtis, Jeffrey L.; et al.
The characteristics that predict progression to overt chronic obstructive pulmonary disease (COPD) in smokers without spirometric airflow obstruction are not clearly defined. We conducted a post hoc analysis of 849 current and former smokers (≥20 pack–years) with preserved spirometry from the Subpopulations and Intermediate Outcome Measures in COPD Study (SPIROMICS) cohort who had baseline computed tomography (CT) scans of lungs and serial spirometry. We examined whether CT-derived lung volumes representing air trapping could predict adverse respiratory outcomes and more rapid decline in spirometry to overt COPD using mixed-effect linear modelling. Among these subjects with normal forced expiratory volume in 1 s (FEV1 ) to forced vital capacity (FVC) ratio, CT-measured residual volume (RVCT ) to total lung capacity (TLCCT ) ratio varied widely, from 21% to 59%. Over 2.5±0.7 years of follow-up, subjects with higher RVCT /TLCCT had a greater differential rate of decline in FEV1 /FVC; those in the upper RVCT /TLCCT tertile had a 0.66% (95% CI 0.06%–1.27%) faster rate of decline per year compared with those in the lower tertile (p=0.015) regardless of demographics, baseline spirometry, respiratory symptoms score, smoking status (former versus current) or smoking burden (pack–years). Accordingly, subjects with higher RVCT /TLCCT were more likely to develop spirometric COPD (OR 5.7 (95% CI 2.4–13.2) in upper versus lower RVCT /TLCCT tertile; p<0.001). Other CT indices of air trapping showed similar patterns of association with lung function decline; however, when all CT indices of air trapping, emphysema, and airway disease were included in the same model, only RVCT /TLCCT retained its significance. Increased air trapping based on radiographic lung volumes predicts accelerated spirometry decline and progression to COPD in smokers without obstruction. Radiographic lung volumes and related computed tomography measures that represent air trapping are associated with an accelerated decline in lung function and can identify susceptible smokers at increased risk of progressing to overt COPD http://bit.ly/32QqiKQ